Impact of transition risks of climate change on Chinese financial market stability - An, Qiguang; Zheng, Lin; Li, Qingzhao; Lin, Chengwei (Frontiers in Environmental Science, 2022)
Transition risks caused by climate change are becoming an important issue in finance research. In this study, we first construct the transmission mechanism of “climate change–change in investor attention–financial stability” and analyze the impact of transition risks on Chinese financial market stability. Second, we construct a Climate Change Index (CCI). The CCI depicts changes in investors’ attention to the transition risks of climate change based on the Baidu Index. We also use the dynamic factor model (DFM) to construct a Financial Stress Index (FSI) that describes the Chinese financial market stability. The FSI can also effectively identify financial events within the sample interval. We then use the TVP-VAR model to empirically analyze the impact of the transition risks of climate change on Chinese financial market stability. We present the following results: in the short and medium terms, more financial market pressure will be caused by an increase in the CCI. In the long run, the impact of an increase in CCI on Chinese financial market pressure is uncertain. Finally, we present valuable countermeasures and suggestions from the different perspectives of investors, financial institutions, and regulators.